2010
DOI: 10.1185/03007991003670563
|View full text |Cite
|
Sign up to set email alerts
|

Impact of persistence with antiplatelet therapy on recurrent ischemic stroke and predictors of nonpersistence among ischemic stroke survivors

Abstract: Persistence with antiplatelet medication within a cohort of hospitalized ischemic stroke patients was associated with a 72.5% lower likelihood of recurrent hospitalized stroke. Higher medication copayment was found to negatively impact patient persistence with antiplatelet therapy. The findings of this study must be considered within the limitations of database analysis, as claims data are collected for the purpose of payment and not research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 18 publications
4
36
1
9
Order By: Relevance
“…Our results on the risk of stroke recurrence in association with discontinuation of antiplatelet treatment are in line with the results of the previous studies, in spite of the varying definitions of discontinuation of antiplatelet use employed in these studies [10,11,19,20]. We note that our results are also in line with those of the only other study that also analysed the recently discontinued antiplatelet use and reported a relative risk of stroke or transient ischaemic attack for recently discontinued antiplatelet use of 1.40 (95% CI: 1.03-1.92) and for past discontinued use of 1.25 (95% CI: 0.81-1.97) [21].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results on the risk of stroke recurrence in association with discontinuation of antiplatelet treatment are in line with the results of the previous studies, in spite of the varying definitions of discontinuation of antiplatelet use employed in these studies [10,11,19,20]. We note that our results are also in line with those of the only other study that also analysed the recently discontinued antiplatelet use and reported a relative risk of stroke or transient ischaemic attack for recently discontinued antiplatelet use of 1.40 (95% CI: 1.03-1.92) and for past discontinued use of 1.25 (95% CI: 0.81-1.97) [21].…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, lifelong use of antiplatelet drugs is recommended in both Danish and international guidelines on stroke treatment [5,6]. However, long-term, nonpersistence and non-adherence to antiplatelet drugs in patients with cerebrovascular disease is a frequent problem [7,8,9], and undermines the beneficial effects of these drugs [10,11]. We designed the present study to determine the relative risk of recurrent stroke or death associated with the discontinuation of antiplatelet drugs in a cohort of stroke patients in Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…Among the patients following treatment protocols, adherence to each isolated class was good, above 85% at 3 years and above 70% at 6 years and when considering the adherence to the 3 associated treatments, corresponding to the optimal preventive therapeutic strategy, adherence was about 70% and it did not decrease between 3 and 6 years. These results are in line with previous studies reporting good adherence within 2 years of stroke based on self-declaration and on the medicoadministrative database using medication possession ratio (MPR >0.8) [21, 23, 24]. Eventually, only 33% of included patients (respectively 70/210 and 53/163) were adherent to the 3 recommended therapeutic classes; that is, combining non-use and non-adherence at 3 and 6 years, 2 out of 3 of patients were not optimally treated to prevent stroke recurrence.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have mainly focused on the persistence of preventive treatment during the 2 years following stroke [13, 14, 21, 25-27]. Three months after discharge, about 65% of patients discontinued at least one secondary preventive treatment [13, 26].…”
Section: Discussionmentioning
confidence: 99%
“…However, patients' adherence to long-term treatments is quite low [3]. Concerning stroke, medication adherence can vary from 45 to 90% [4,5,6,7,8,9]. It has been proven that poor adherence results in poor treatment outcomes [7,10,11].…”
Section: Introductionmentioning
confidence: 99%